Norovirus as the cause of medically attended gastroenteritis: a hospital-based experience - GASTAÑADUY, A. S.; ZABALETA, J.; LI, L.; BÉGUÉ, R. E. (Epidemiology and infection, 2016)
Gastroenteritis remains an important cause of morbidity and mortality worldwide. With the introduction of vaccines against rotavirus, interest has shifted to understanding the epidemiology of norovirus (NoV). While the importance of NoV in gastroenteritis outbreaks is well established, its role in sporadic gastroenteritis is less known. To better define the role of NoV as a cause of sporadic gastroenteritis we investigated its prevalence in the patients seen in our paediatric hospital with special emphasis on its seasonal and age distribution. Over a 12-month period discarded stool specimens submitted to our paediatric hospital for testing of an infectious aetiology were retrieved and additionally tested for NoV by real-time reverse transcriptase–polymerase chain reaction; demographical and clinical information were also obtained. Overall, NoV was the single most commonly identified pathogen and found in 68/892 (7·6%) total specimens or 68/258 (26%) of pathogen-positive specimens. The highest rates of NoV were detected in children aged 6 months to 4 years (50/332, 15·1%) and presenting between October and January (46/314, 14·7%). NoV has become the main cause of gastroenteritis in our paediatric population.